Supplement Use and Doping Risk Across Menstrual Cycle Phases in Female Athletes - Rafa Dinnantra Limastyningrum; Muhammad Rifky Arifin; Sheva Naufal Fadillah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The menstrual cycle is a physiological factor influencing health status, nutritional requirements, and athletic performance in female athletes. Hormonal fluctuations across menstrual cycle phases encourage the use of various sports supplements to support performance, recovery, and management of menstrual symptoms. However, supplement use may also increase the risk of accidental doping due to contamination of consumed products with prohibited substances. This study aimed to examine the relationship between sports supplement use across menstrual cycle phases and doping risk among female athletes. A Systematic Literature Review (SLR) method following PRISMA guidelines was employed, with literature retrieved from Google Scholar, PubMed, ScienceDirect, and SpringerLink databases covering 2015-2025. A total of 10 articles meeting the inclusion criteria were analyzed using a thematic analysis approach. Findings indicate that menstrual cycle phase influences both nutritional needs and supplement-use patterns among female athletes. The most commonly used supplements include iron, protein, caffeine, creatine, vitamin D, magnesium, and omega-3 fatty acids. Although these supplements support athletic performance and overall health, uncontrolled use may increase the risk of accidental doping. Therefore, education on safe supplement use and menstrual cycle monitoring is essential as part of a comprehensive strategy to support the performance and well-being of female athletes.